“Great to see ur staff are doing their job properly”: Customer (dis)affiliation on corporate Facebook pages - Palomino-Manjón, Patricia (International Journal of English Studies, 2018)
The emergence of new technologies has changed the way people communicate. Social media have allowed businesses to connect with customers and to market their products more efficiently. However, these platforms also allow customers to share information and opinions with the company and fellow customers, diverting from previous online service encounters which only allowed the interaction between the service provider and the customer. This new digital space of communication is in need of research. Therefore, the main objective of this paper is to analyze how customer (dis)affiliation is discursively realized on Facebook. To do so, a corpus of comments published by customers on the Facebook page of a British grocery chain was compiled. The data were analyzed drawing on Appraisal Theory (Martin & White, 2005). The findings show that customers used a varied range of Appraisal resources to evaluate the company and express (dis)affiliation with it and fellow customers.